2004
DOI: 10.1038/sj.bmt.1704746
|View full text |Cite
|
Sign up to set email alerts
|

Successful haemopoietic stem cell transplantation does not correct mannan-binding lectin deficiency

Abstract: Summary:It has been reported that in allogeneic stem cell transplantation, the mannan-binding lectin (MBL) status of the donor has prognostic value for the recipient. Two MBL-deficient patients, with coexisting haematological malignancy, were identified who were treated with bone marrow from donors with normal MBL concentrations. Although both patients engrafted successfully and remain in complete remission, neither seroconverted to the MBL sufficiency status of his donor over a follow-up period exceeding 2 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 10 publications
2
15
0
Order By: Relevance
“…12 Moreover, the MBL genotype of the liver donor, not that of the recipient, determined the risk for potential lifethreatening infections after liver transplantation. 12 In this study we confirm the observation by others that MBL levels and occurrence of infections in the HSCT recipients were not influenced by donor MBL status, 13 which is not in line with the findings of Mullighan et al 7 who showed that donor MBL2 genotype influenced the occurrence of infections in recipients. Recombinant human MBL replacement therapy is currently studied in clinical trials involving patients receiving intensive chemotherapy, allogeneic HSCT or liver transplantation.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…12 Moreover, the MBL genotype of the liver donor, not that of the recipient, determined the risk for potential lifethreatening infections after liver transplantation. 12 In this study we confirm the observation by others that MBL levels and occurrence of infections in the HSCT recipients were not influenced by donor MBL status, 13 which is not in line with the findings of Mullighan et al 7 who showed that donor MBL2 genotype influenced the occurrence of infections in recipients. Recombinant human MBL replacement therapy is currently studied in clinical trials involving patients receiving intensive chemotherapy, allogeneic HSCT or liver transplantation.…”
Section: Discussionsupporting
confidence: 74%
“…12 Whether the donor MBL status has an impact on the MBL status or infection susceptibility of the recipient post-HSCT is unclear. 7,13 We studied this in a cohort of 98 pediatric allogeneic HSCT recipients and their donors.…”
Section: Introductionmentioning
confidence: 99%
“…The association with donor MBL2 genotype suggested that donor-derived hematopoietic tissues and their progeny might contribute clinically significant quantities of MBL after transplantation. However, a recent study of a small number of MBL2-deficient allogeneic hematopoietic stem cell transplant recipients failed to observe correction of MBL levels after receiving a transplant from an MBL-sufficient donor, 21 thus questioning the importance of donor-derived MBL synthesis after BMT. The current study has again observed associations of both recipient and donor MBL2 genotype with infection risk in univariable analysis.…”
Section: Discussionmentioning
confidence: 99%
“…The issue of association of increased infection risk in haematopoietic stem cell transplant recipients from donors with variant MBL2 genotype remains unresolved but more likely, the major association is with recipient MBL2 genotype as MBL is produced in the liver. Additionally, haematopoietic stem cell transplant using wildtype MBL2 cells has been shown to not correct low MBL levels in recipients with variant MBL2 genotype [59] .…”
Section: Mbl Deficiency and Fungal Respiratory Tract Infectionsmentioning
confidence: 99%